Insights in the rheological properties of PLGA-PEG-PLGA aqueous dispersions: Structural properties and temperature-dependent behaviour. (20th January 2021) - Cespi, Marco; Bonacucina, Giulia; Tiboni, Mattia; Casettari, Luca; Cambriani, Alessandra; Fini, Francesco; Perinelli, Diego Romano; Palmieri, Giovanni Filippo
Abstract: PLGA-PEG-PLGA are copolymers, able to form temperature-dependent hydrogels or sol dispersions at selective conditions. A general overview about the rheological characterization of their aqueous dispersions, focusing how the structural characteristics (e.g. molecular weight, PEG/PLGA ratio) affect their temperature-dependent behaviour, is presented. Different PLGA-PEG-PLGA were synthesized by varying the amount of lactide and glycolide and the amount and molecular weight of PEG. All polymers were characterized by gel-permeation chromatography and differential scanning calorimetry. Then, polymeric dispersions in water (15%–25% w/w) were analysed by oscillatory rheological measurements. At solid state, all copolymers are amorphous and the calculated glass transition temperatures were dependent on PEG/PLGA ratio. As regard aqueous dispersions, the temperature-dependent rheological behaviour named "partially thermogelling" has been described, in addition to the commonly reported thermogelling one. In these samples, the consistency increases over temperature without forming a three-dimensional network as for real hydrogels. All rheological characteristics can be explained according to the proposed categorization (thermogel, partial thermogel and sol dispersion). Graphical abstract: Image 1 Highlights: All PLGA-PEG-PLGA copolymers are amorphous; T g values were dependent on the PEG/PLGA. Aqueous dispersions were categorised in terms of temperature-dependent behaviour. Partial thermogelling, thermogelling and sol rheological behaviours were described. In partially thermogels, consistency increases over temperature without a 3D network. Thermogels were observed for copolymers having a PEG/PLGA ratio around 0.45–0.5.